2014
DOI: 10.1002/cam4.167
|View full text |Cite
|
Sign up to set email alerts
|

HER2 overexpression a major risk factor for recurrence in pT1a‐bN0M0 breast cancer: results from a French regional cohort

Abstract: The management of pT1a-bN0M0 breast cancer remains an area of controversy. Data from 714 patients classified as having pT1a-bN0M0 breast cancer and treated, from 1999 to 2004 in the Languedoc-Roussillon France, were analyzed. The human epidermal growth factor receptor 2 (HER2) status analyses were centralized. The objective of this study was to describe the prognosis of pT1a-bN0M0 breast cancer according to HER2 distribution and hormonal status. The median follow-up was 6.4 years. Ten-year overall survival was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
(51 reference statements)
1
25
2
Order By: Relevance
“…In recent years there is increasing evidence that it is not only the tumor size itself but also biological features which are predictive for the outcome of patients, especially for T1a/b breast cancers. Factors like HER2-overexpression or negative hormone receptor (HR) status seem to have more impact on the prognosis of the patients than tumor size [8][9][10][11][12]. Until recently, it was generally accepted that especially T1a breast cancers do not require adjuvant systemic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there is increasing evidence that it is not only the tumor size itself but also biological features which are predictive for the outcome of patients, especially for T1a/b breast cancers. Factors like HER2-overexpression or negative hormone receptor (HR) status seem to have more impact on the prognosis of the patients than tumor size [8][9][10][11][12]. Until recently, it was generally accepted that especially T1a breast cancers do not require adjuvant systemic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, from a French regional cohort, HER2 over-expression is proved to be a major risk factor for recurrence in pT1a-bN0M0 breast cancer (Rouanet et al, 2014). Also, HER2 over-expression was associated with locoregional recurrence (LRR) in the pre-adjuvant trastuzumab era (Lanning et al, 2015).…”
Section: Other Associated Micromoleculesmentioning
confidence: 99%
“…Some retrospective analyses of patients with small HER2‐positive cancers have demonstrated worse outcomes compared with those achieved in patients with other breast cancer subtypes . In contrast, the results of other studies have indicated that outcomes are more favorable, with low recurrence rates reported in patients with small HER2‐positive breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective analyses have demonstrated that patients with small HER2‐positive breast cancers have inferior outcomes compared with those of patients with other breast cancer subtypes. However, recent data have challenged this concept and demonstrated favorable outcomes for patients with small HER2‐positive breast cancers (Table ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation